2015
DOI: 10.1021/acs.joc.5b01766
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Ferrocene Oxazoline N,O ligands and Their Application in Asymmetric Ethyl- and Phenylzinc Additions to Aldehydes

Abstract: The synthesis of a range of novel gem-disubstituted ferrocene-oxazoline ligands and their application in both the asymmetric ethyl- and phenylzinc additions to aldehydes is reported. These studies reveal that gem-disubstitution of i-Pr-containing ferrocene oxazoline ligands results in increased enantioselectivity compared to their unsubstituted counterparts. Utilizing zinc catalysis, these ligands provided a wide range of secondary alcohols in yields of up to 93% with ee's of up to >99%. An interesting crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 45 publications
0
24
0
1
Order By: Relevance
“…Palladium complexes of ligands 5 and 6a,b were applied by us in the intermolecular asymmetric Heck reaction with ee values of up to 97%. 43 Complex 5 did induce high levels of enantioselectivity, even with significantly different dihedral angles of −38°and −159°to ligands of type 6. In addition, in the present study, the two ligands 11b and 11c, which exhibit dihedral angles of −177°/−56°and −177°/−55°, respectively, are not significantly inferior to ligands 11a and 11d.…”
Section: Scheme 7 Preparation Of Zinc Dichloride Complex (19) Derivementioning
confidence: 91%
See 1 more Smart Citation
“…Palladium complexes of ligands 5 and 6a,b were applied by us in the intermolecular asymmetric Heck reaction with ee values of up to 97%. 43 Complex 5 did induce high levels of enantioselectivity, even with significantly different dihedral angles of −38°and −159°to ligands of type 6. In addition, in the present study, the two ligands 11b and 11c, which exhibit dihedral angles of −177°/−56°and −177°/−55°, respectively, are not significantly inferior to ligands 11a and 11d.…”
Section: Scheme 7 Preparation Of Zinc Dichloride Complex (19) Derivementioning
confidence: 91%
“…43 In addition, it is useful to compare the dihedral angles with the palladium complex of ligand 21 (t-Bu PHOX). 39 The corresponding dihedral angles N 1 −C 5 −C 6 −C 7 and N 1 − C 5 −C 6 −C 8 for the palladium complex of ligand 21 are −80°a nd 58°, entry 11, in line with the dihedral angles observed for ligand 11a (−79°and 46°), entry 1, and the iron complex of ligand 11d (−77°and 50°), entry 4.…”
Section: Scheme 7 Preparation Of Zinc Dichloride Complex (19) Derivementioning
confidence: 99%
“…[53] This protocol has also been shown to work on the diastereoselectiveo rtholithiation of ferrocenes. [53,56,57] Nevertheless, even better ICC diastereoselectivities, of up to 120:1 with various electrophiles, can be obtained when using a tert-butyl oxazoline (not shown). [54] The oxazoline can then be removed through hydrolysis to give pure non-racemic meta-functionalised ICCs.…”
Section: Meta-functionalisationmentioning
confidence: 99%
“…These studies have revealed some interesting results such as the ability to change the overall diastereoselectivity of the reaction through careful ligand choice (Scheme ) and thus avoid the need to use both enantiomers of the chiral isopropyl oxazoline calix[4]arene 28 . This protocol has also been shown to work on the diastereoselective ortholithiation of ferrocenes . Nevertheless, even better ICC diastereoselectivities, of up to 120:1 with various electrophiles, can be obtained when using a tert ‐butyl oxazoline (not shown) .…”
Section: Meta‐functionalisationmentioning
confidence: 99%
“…We note that none of the top-three approaches found by Chematica in single-targetoriented searches for A1 (Fig. 5a-c and S5 †) relying on either the Friedel-Cras acylation with carbamate protected b-aminopropionic acid 50 or enantioselective arylation of aldehydes 51,52 are desirable for the design of the entire library. This is so because these syntheses cannot take advantage of late common intermediates and require several additional reactions (e.g., for the optimal individual solution to A1, adaptation to the alllibrary synthesis would entail a total of 21 distinct reactions (allylation, four displacements with phenols, four hydroborations, and twelve aminations).…”
Section: Synthesis Of All Members Of a Prozac-derived Librarymentioning
confidence: 99%